2005
DOI: 10.1111/j.1540-8175.2005.40051.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Imaging Identifies Asymptomatic Normotensive Diabetics with Diastolic Dysfunction and Reduced Exercise Tolerance

Abstract: Differently from classical criteria based on pulsed Doppler, Tissue Doppler imaging identifies a group of asymptomatic normotensive diabetics with diastolic dysfunction and reduced exercise tolerance. Confirmation of the prognostic importance of our findings could justify the use of Tissue Doppler imaging for diastolic function assessment in diabetics with otherwise healthy hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…On the other hand, Saraiva et al [45] stated in their study that "tissue Doppler imaging identified diastolic dysfunction in 26.6% of diabetics, while classical criteria did so in 40.5% of the cases. The group identified by classical criteria did not differ significantly from patients without diastolic dysfunction, while in the group identified by TDI, significant differences were highlighted".…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, Saraiva et al [45] stated in their study that "tissue Doppler imaging identified diastolic dysfunction in 26.6% of diabetics, while classical criteria did so in 40.5% of the cases. The group identified by classical criteria did not differ significantly from patients without diastolic dysfunction, while in the group identified by TDI, significant differences were highlighted".…”
Section: Discussionmentioning
confidence: 93%
“…The transmitral peak filling velocity E was significantly enhanced in our diabetes patients reflecting that the increased E/E′ ratio was driven by E and not by E′, which is in contrast to another study demonstrating impaired relaxation (E′) in diabetes patients. 6 Takeda et al, however, did not find E′ to be a significant determinant of heart failure in diabetes patients with preserved ejection fraction. They concluded that the progression from asymptomatic stage to diastolic heart failure may be induced by worsening of LV compliance rather than LV relaxation.…”
Section: Function and Agesmentioning
confidence: 90%
“…Echocardiographic Doppler transmitral flows, tissue Doppler and MRI reliably detect functional abnormalities such as impairment (prolongation) of LV filling or LV relaxation, and/or reduced diastolic distensibility [22][23][24][25][26]. Conservative estimates now suggest that diastolic dysfunction is present in 50% (or more) of asymptomatic, normotensive patients with well-controlled diabetes, preserved left ventricular (LV) ejection fraction and no overt coronary artery disease [23,27,28]; this contributes to a 4 to 8-fold increase in the risk of heart failure in these patients, which often progresses to sudden death [22]. Systolic dysfunction (e.g., reduced LV ejection fraction), as well as metabolic disturbances, myocardial fibrosis and cardiac autonomic neuropathy, may also be evident [5,6,22].…”
Section: Evidence Of Myocardial Dysfunction In the Insulin-resistant mentioning
confidence: 99%